Temporal trends in intracerebral hemorrhage in a general population. Incidence, risk factors, case fatality and long-term mortality. The Tromsø Study - Carlsson, Maria (UiT The Arctic University of Norway, 2021)
Intracerebral hemorrhage (ICH) is the second most common subtype of stroke. The prognosis is poor. However, it is to a large degree a preventable disease. The aim of our study was to analyse the association between cardiovascular risk factors and risk of ICH, and to assess the impact of changes in risk factor levels over time on incidence rates of ICH. In addition, we aimed to analyse short- and long-term mortality after ICH. The Tromsø study is an ongoing, longitudinal population-based study with repeated health surveys, with >45,000 attendees, providing an unique opportunity to assess longitudinal data on ICH epidemiology in a general population in a well-defined geographical area. Age, male sex, systolic and diastolic blood pressure were significantly associated with increased risk of ICH. Incidence rates were stable in the overall population in the period 1995-2013. In women incidence rates decreased, whereas incidence rates in men were stable. Lower blood pressure levels, and a steeper decrease in blood pressure in women may have contributed to the difference in trends. Despite an increase in treatment of hypertension, less than half of attendees of the last survey who had hypertension were on blood pressure-lowering drugs. Of these, two-thirds had uncontrolled hypertension. One-month case fatality and 5-year mortality rates remained stable. Participants who survived the first 30 days after ICH had a more than 60% increased 5-year risk of death compared with controls matched by birth-year and sex. The main cause of death was cardiovascular disease. Smoking, serum cholesterol and use of anticoagulant drugs at time of ICH were associated with increased risk of 5-year mortality after ICH. Our results indicate that there is a need for improved primary prevention of ICH. The stable short- and long-term mortality rates probably reflect the limited treatment possibilities of ICH and emphasize the urge for improved treatment strategies in the acute phase and a need for better knowledge on secondary prevention ...